8x+38=-2(-19-4x)x=

Simple and best practice solution for 8x+38=-2(-19-4x)x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+38=-2(-19-4x)x= equation:



8x+38=-2(-19-4x)x=
We move all terms to the left:
8x+38-(-2(-19-4x)x)=0
We add all the numbers together, and all the variables
8x-(-2(-4x-19)x)+38=0
We calculate terms in parentheses: -(-2(-4x-19)x), so:
-2(-4x-19)x
We multiply parentheses
8x^2+38x
Back to the equation:
-(8x^2+38x)
We get rid of parentheses
-8x^2+8x-38x+38=0
We add all the numbers together, and all the variables
-8x^2-30x+38=0
a = -8; b = -30; c = +38;
Δ = b2-4ac
Δ = -302-4·(-8)·38
Δ = 2116
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{2116}=46$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-30)-46}{2*-8}=\frac{-16}{-16} =1 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-30)+46}{2*-8}=\frac{76}{-16} =-4+3/4 $

See similar equations:

| -3(1+3x)=2(4x+7)= | | ⅓a–12=⁴/³a+6 | | W-2(w-6)=6 | | 324=a^ | | -5k-3+3k=5 | | 5y(2.3-1)=y(3+2)+20 | | 8(x+3)-2=2x+10 | | X/187=2x+5(3x+14) | | 4p+(-5)=-17 | | 8z+12=5z-1(21z+4) | | a-6=10-a | | 6+x+2x=21 | | 11=3x+26 | | -1t+-8=-7.1 | | ​6x+20−x=80 | | 24x+12-16+15=75 | | 15+4x-6+6=7 | | -3(x+5)=2(4x+9) | | 2/3(9x+18)-2x=1/4(16x+48) | | 3x-5+x+55=90 | | -11(5y-3)-2y=8(-7y+3) | | 2+9x+8x-9=180 | | 5x^2=4x+3 | | 60+1x=180 | | 285-5x=340-10x | | t/3+(-1)=0 | | -6c+10=-7c | | 7-8774654+764735x=34x+938(x-902x) | | 3m-5+6m=-5 | | 4y×4y+3y=10×10 | | 4y-2y=-1+13 | | 2v—1=7 |

Equations solver categories